Comparative study of ultrasound-guided in-plane and anatomical landmark cannulation of infraclavicular subclavian vein in intensive care unit – a prospective randomized control trial. - Lathika G; Elakkiya.G; Rajaram M; Periasamy, Panneerselvam (Student's Journal of Health Research Africa, 2025)
Background: Subclavian vein cannulation is a critical procedure in the intensive care unit (ICU) for administering medications, fluids, and hemodynamic monitoring. Traditional anatomical landmark techniques, while widely practiced, are associated with higher complication rates. The use of ultrasound-guided techniques has emerged as a safer alternative with improved success rates. Objectives: To compare ultrasound-guided in-plane cannulation and anatomical landmark cannulation of the infraclavicular subclavian vein in terms of success rates, complication rates, procedural time, and hemodynamic changes in ICU patients. Materials and methods: This prospective randomized controlled trial included 60 ICU patients requiring subclavian vein cannulation, who were randomly assigned to two groups: Group U (ultrasound-guided, n=30) and Group L (landmark-guided, n=30). Primary outcomes included time to locate the subclavian vein and the number of attempts. Secondary outcomes were success rate, failure rate, complications, and hemodynamic changes. Data were analyzed using appropriate statistical tests. Results: The groups were comparable in baseline demographics. The mean time to locate the vein was 4.0 ± 1.0 minutes in Group U and 4.2 ± 1.0 minutes in Group L (p = 0.44). The success rate was higher in Group U (87%) compared to Group L (85%), while the corresponding failure rates were 13% and 15% respectively, though differences were not statistically significant (p = 0.59). Complications were slightly lower in the ultrasound group (18%) versus the landmark group (20%) (p = 0.72). Heart rate changes post-cannulation remained stable in both groups, with a significant difference noted only at 5 minutes (p = 0.05). Conclusion: Ultrasound-guided in-plane subclavian vein cannulation demonstrates slightly higher success rates, fewer complications, and comparable procedural time, confirming its clinical advantage over the anatomical landmark technique in ICU settings. Recommendations: Ultrasound-guided subclavian vein cannulation should be routinely implemented in ICUs to enhance safety, procedural success, and patient outcomes.